Spectrum efficiency in cellular mobile radio systems with multiple correlated signals - Şafak, Aysel (IEEE, 1994)
Spectrum efficiency is evaluated in cellular mobile radio systems considering multiple correlated log-normal signals with and without Rayleigh fading environment. The effect of fading and shadowing on spectrum efficiency is investigated in terms of the probability of co-channel interference (PCI). The paper addresses as well the influence of the traffic load and call blocking probability on the spectrum efficiency.
Proceedings of the 7th Mediterranean Electrotechnical Conference - MELECON. Part 1 (of 3) --
Keywords: Communication channels (information theory); Correlation methods; Correlation theory; Correlators; Fading (radio); Frequency modulation; Mathematical models; Parametric devices; Probability; Radio interference; Spectrum analysis; Telecommunication traffic; High density reuse; Log normal shadowing; Multiple correlated signals; Narrowband transmission; Probability of cochannel interference; Rayleigh fading; Shwartz analytical method; Yeh analytical method; Cellular radio systems